Modulation instability and dissipative ion-acoustic structures in collisional nonthermal electron-positron-ion plasma: solitary and shock waves5The project is supported by NSF of China (11501441, 11371289, 11371288), National Natural Science Foundation of China (U1261112), China Postdoctoral Science Foundation (2014M560756), and Fundamental Research Funds for the Central Universities (xjj2015067). (10th August 2016) - Guo, Shimin; Mei, Liquan; He, Ya-Ling; Ma, Chenchen; Sun, Youfa
Abstract: The nonlinear behavior of an ion-acoustic wave packet is investigated in a three-component plasma consisting of warm ions, nonthermal electrons and positrons. The nonthermal components are assumed to be inertialess and hot where they are modeled by the kappa distribution. The relevant processes, including the kinematic viscosity amongst the plasma constituents and the collision between ions and neutrals, are taken into consideration. It is shown that the dynamics of the modulated ion-acoustic wave is governed by the generalized complex Ginzburg–Landau equation with a linear dissipative term. The dispersion relation and modulation instability criterion for the generalized complex Ginzburg–Landau equation are investigated numerically. In the general dissipation regime, the effect of the plasma parameters on the dissipative solitary (dissipative soliton) and shock waves is also discussed in detail.